The Polar Code (Comments in Foreign Legal Sources) - Alexander N. Vylegzhanin; Georgy G. Ivanov; Inna P. Dudikina (Московский журнал международного права, 2015)
The paper addresses the content of a new International document - the International Code for Ships Operating in Polar Waters- in the context of foreign teachings on the subject. Special attention is devoted to the legal significance of the Polar Code and its relation to other sources of the Law of the Sea, including the UN Convention on the Law of the Sea, 1982.